PENGARUH METODE BERMAIN PERAN TERHADAP KECERDASAN EMOSIONAL ANAK USIA 4-5 TAHUN DI RA BUNDA SUWARNI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Fatmaliza, Fatmaliza; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine the emotional intelligence before the method of playing a role in children aged 4-5 years in RA Bunda Suwarni District of Marpoyan Peace Pekanbaru. 2) To know the emotional intelligence as a method of playing a role in children aged 4-5 years in RA Bunda Suwarni District of Marpoyan Peace Pekanbaru. 3) To determine the effect of the method of playing the role of emotional intelligence in children aged 4-5 years RA Bunda Suwarni Marpoyan Peace District of the city of Pekanbaru. This type of research used in this research is the experimental approach of a study that sought influence of certain variables on other variables in strictly controlled conditions. In this case that is the subject of this research is in RA Bunda Suwarni District of Marpoyan Peace Pekanbaru City with the number of children 15, 7 boys and 8 girls. Collecting data using observation and documentation. Based on the survey results revealed that 1) the ability of emotional intelligence of children aged 4-5 years in RA Bunda Suwarni District of Marpoyan Peace Pekanbaru before treatment is given in the form of role-playing method is low. 2) The ability of emotional intelligence of children aged 4-5 years in RA Bunda Suwarni District of Marpoyan Peace Pekanbaru City after being given treatment in the form of a method of playing a role has increased and is high. 3) Method of playing a role has a significant impact on the ability of emotional intelligence of children aged 4-5 years in RA Bunda Suwarni District of Marpoyan Peace Pekanbaru. It can be seen that there are differences related to increase the child's emotional intelligence before and after treatment. Method of playing a role has the effect of 33.48% of the emotional intelligence abilities of children aged 4-5 years in RA Bunda Suwarni District of Marpoyan Peace Pekanbaru.Keywords: Role Playing, Emotional Intelligence